Novel diamond shaped UWB monopole antenna - Singhal S.; Goel T.; Singh A.K. (My University, 2025)
A novel compact microstrip line fed diamond shaped monopole antenna for Ultra Wideband (UWB) applications is proposed. The antenna structure consists of a diamond shaped radiating patch and a semicircular like ground plane. The radiating patch is derived from a conventional rectangular patch antenna. The simulated results show that the impedance bandwidth (VSWR ≤ 2) of the proposed antenna ranges from 0.8409 to 15.5109 GHz (179.4%) and 16.7679 to 18.3753 GHz (9.15%). © 2013 IEEE.